The variants of polymyxin susceptibility in different species of genus Aeromonas - Xu, Linna; Fan, Junfeng; Fu, Hao; Yang, Yuyi; Luo, Qixia; Wan, Fen (Frontiers in Microbiology, 2022)
The aquatic environment is an important medium for the accumulation and dissemination of antibiotic-resistant bacteria as it is often closely related to human activities. Previous studies paid little attention to the prevalence and mechanism of polymyxin-resistant bacteria in the aquatic environment. As a Gram-negative opportunistic pathogen widely distributed in aquatic ecosystems, the antibiotic-resistant profile of Aeromonas spp. deserves much attention. In this study, we identified 61 Aeromonas spp. isolates from water samples in the section of the Yangtze River. The total polymyxin B (PMB) resistance rate of these strains was 49.18% (30/61), showing a high level of colistin resistance. The MIC50 and MIC90 for PMB exhibited a significant discrepancy among different species (P< 0.001). The MIC50 and MIC90 for PMB in the Aeromonas hydrophila were 128 mg/L and above 128 mg/L while in Aeromonas caviae and Aeromonas veronii the MIC50 and MIC90 value were both 2 mg/L. Only two A. veronii strains (MIC = 2 mg/L) and one A. caviae strain (MIC = 0.5 mg/L) were identified as carrying mobilized polymyxin resistant gene mcr-3.42, and mcr-3.16. All mcr genes were located in the chromosome. This is the first report that the downstream of mcr-3.42 was the truncated mcr-3-like gene which was separated by the insertion sequences of ISAs20 (1674 bp) and ISAs2 (1084 bp). Analysis of epidemiology of mcr-positive Aeromonas genomes from GenBank database showed that the genus Aeromonas and the aquatic environment might be the potential container and reservoir of mcr-3. By the sequence alignment analysis, we inferred that the differences in the AAA domain of MlaF protein and its expression level among these three species might be involved in the development of polymyxin resistance. Our study provided evidences of the possible mechanism for the different polymyxin susceptibility in different species of the genus Aeromonas and a theoretical basis for the surveillance of the aquatic environment.